Utility of island populations in re‐introduction programmes – relationships between Arabian gazelles (Gazella arabica) from the Farasan Archipelago and endangered mainland populations. Issue 8 (24th March 2014) - Lerp, Hannes; Plath, Martin; Wronski, Torsten; Bärmann, Eva V.; Malczyk, Anna; Resch, Revina‐Rosa; Streit, Bruno; Pfenninger, Markus
Abstract Understanding local adaptation and population differentiation is vital to the success of re‐introduction initiatives. As other mammals living on islands, Arabian gazelles (G. arabica) show reduced body size on the Farasan archipelago, which we corroborated in this study through morphometric analyses of skulls. In the light of the steep population decline on the Arabian Peninsula – but stable population development on the archipelago – we tested the potential suitability of Farasan gazelles as a source for re‐introductions on the mainland. We therefore investigated genetic differentiation between Farasan and mainland populations using eleven nuclear microsatellite loci and detected a distinct genetic cluster exclusively present on the archipelago, which we inferred to be separated from the mainland cluster for less than 2000 years. About 30% of sampled individuals from Farasan Islands showed assignment to a mainland cluster with signs of ongoing introgression. Analyses using the isolation‐with‐migration model confirmed recent (probably human‐induced) bidirectional exchange of gazelles between mainland and island populations. Hence, the surprisingly uniform island dwarfism most likely reflects phenotypic plasticity, that is, altered morphology as a direct consequence of harsh environmental conditions and resource limitation on the archipelago. Should a further decline of Arabian gazelles on the mainland necessitate restocking in the future, Farasan gazelles may thus become an additional source for captive breeding programmes.